Supply Strategy: A Quasi-Experiment on the Number And Location of Suppliers - André Luis de Castro Moura Duarte (FUCAPE Business School, 2017)
Objective: Evaluate the impact of a second supply source on price, quality and stock levels at the purchasing company. Relevance: The supply strategy defines how many suppliers an item should have and where it should be located. If working with a single supplier may bring relational benefits, working with multiple sources may reduce opportunism risks. If a local supplier reaps benefits on account of its proximity, a global supplier may result in lower costs. Methodology: The quasi-experimental method was used to follow-up a purchasing policy change at an auto parts company, which took on a second supply source for low complexity items. The research collected data on costs, quality and stock coverage for 1,480 items between 2007 and 2012, analysing new supplier’s entrance and location. Results: Introducing a second supplier reduced the price, especially when a new international supplier was introduced. Decreases in quality or increases in stock coverage were not observed.